Directed evolution of AMS8 lipase towards enhanced activity and stability at low temperature - Arulu, Pireya Tharaseni (2017)
Cold active lipases have huge biotechnological prospects due to their high catalytic activity at low temperature. Generally, cold active lipases demonstrates high specific activity at low temperature and rapidly denatured in moderate range of temperature due to their thermosensitive nature. However, the factor that contributes to this cold adaptation properties are still vague. AMS8 lipase is a Family 1.3 lipase produced by Antarctic Pseudomonas sp exhibits minimum activity at low temperature. The aim of this study is to evolve AMS8 lipase with enhanced activity and stability at low temperature and to study the effect of the amino acid substitution on the biochemical features of this lipase. The mutant library of AMS8 lipase was generated by error-prone PCR. Mutant M15 lipase was selected as it has the highest lipolytic activity at 20°C. M15 lipase was sequenced and two mutation points were identified which are R259C and V342E. In silico studies of this mutant has predicted that M15 lipase has increased structural flexibility compared to the native enzyme. Mutant M15 lipase was purified using gel filtration chromatography method. Biochemical characterization has revealed that M15 lipase has an optimum temperature at 20°C and highly stable at 10°C. M15 lipase was optimally active at pH 6 and stable within a small range of pH, 6-10. The catalytic activity of the mutant was boosted in the presence of Ca2+ and Na+. Moreover, M15 lipase was found to be tolerant towards hydrophobic organic solvents and demonstrated great specificity towards long-chain pNP esters and optimum activity was observed in pNP-laurate. Secondary structure analysis of M15 lipase revealed that the enzyme has attained more structural flexibility compared to the wild type. In conclusion, AMS8 lipase was successfully mutated via directed evolution strategy and the findings will be useful insight on the understanding of the cold active lipases properties.